Change of direction ability test differentiates higher level and lower level soccer referees - J Yanci; A Los Arcos; I Grande; JA Casajús (Termedia Publishing House, 2016)
This report examines the agility and level of acceleration capacity of Spanish soccer referees and investigates the possible differences between field referees of different categories. The speed test consisted of 3 maximum acceleration stretches of 15 metres. The change of direction ability (CODA) test used in this study was a modification of the Modified Agility Test (MAT). The study included a sample of 41 Spanish soccer field referees from the Navarre Committee of Soccer Referees divided into two groups: i) the higher level group (G1, n = 20): 2ndA, 2ndB and 3rd division referees from the Spanish National Soccer League (28.43 ± 1.39 years); and ii) the lower level group (G2, n = 21): Navarre Provincial League soccer referees (29.54 ± 1.87 years). Significant differences were found with respect to the CODA between G1 (5.72 ± 0.13 s) and G2 (6.06 ± 0.30 s), while no differences were encountered between groups in acceleration ability. No significant correlations were obtained in G1 between agility and the capacity to accelerate. Significant correlations were found between sprint and agility times in the G2 and in the total group. The results of this study showed that agility can be used as a discriminating factor for differentiating between national and regional field referees; however, no observable differences were found over the 5 and 15 m sprint tests.